1996
DOI: 10.1021/np960376j
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antiplatelet Constituents from Formosan Moraceous Plants

Abstract: Sixteen constituents from Formosan Moraceous plants were tested for their antiplatelet activities in rabbit platelet suspension and human platelet-rich plasma. Cycloartocarpin A, cycloheterophyllin, broussochalcone A, kazinol A, broussoaurone A, and broussoflavonol F showed strong inhibition of arachidonic acid (AA)-induced platelet aggregation. Of the compounds tested, broussochalcone A exhibited the most potent inhibition of platelet aggregation induced by AA (IC50 = 6.8 microM). The antiplatelet effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 8 publications
1
37
0
2
Order By: Relevance
“…The following report also demonstrated that several preny- lated flavonoids including kuwanons and sanggenon D were COX inhibitors (27). Several prenylated flavonoids such as cycloheterophyllin, broussochalcone A, broussoaurone A, and broussoflavonol F inhibited platelet aggregation and inhibited COX from ram seminal vesicle (IC 50 of 17.5 -26.1 mg/ ml) (28). Recently, some other prenylated flavonoids including kuraridin, kurarinone, and sophoraflavanone G were found to possess potent COX-1 inhibitory activity from bovine platelet homogenate at micromolar concentrations (IC 50 = 0.1 -1 mM), being comparable to indomethacin (IC 50 = 0.9 m M) (29).…”
Section: Cellular Action Mechanismsmentioning
confidence: 65%
“…The following report also demonstrated that several preny- lated flavonoids including kuwanons and sanggenon D were COX inhibitors (27). Several prenylated flavonoids such as cycloheterophyllin, broussochalcone A, broussoaurone A, and broussoflavonol F inhibited platelet aggregation and inhibited COX from ram seminal vesicle (IC 50 of 17.5 -26.1 mg/ ml) (28). Recently, some other prenylated flavonoids including kuraridin, kurarinone, and sophoraflavanone G were found to possess potent COX-1 inhibitory activity from bovine platelet homogenate at micromolar concentrations (IC 50 = 0.1 -1 mM), being comparable to indomethacin (IC 50 = 0.9 m M) (29).…”
Section: Cellular Action Mechanismsmentioning
confidence: 65%
“…Several previous studies reported the characterization of prenylflavonoids from A. heterophyllus [7 -9] and their anti-inflammatory [10], antioxidant [11,12], melanin-biosynthesis inhibitory [13], and antiplatelet [14] activities. In addition, extract of the wood of A. heterophyllus was reported to inhibit tyrosinase activity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, artocarpin (2) also showed antioxidant activities by reducing the level of reactive oxygen species and lipid peroxidation, and exhibited anti-inflammatory activity by decreasing the levels of pro-inflammatory cytokines, such as tumor necrosis factor a and interleukin 1b (Lee et al, 2013) and inhibited lipopolysaccharide-induced nitric oxide (NO) production (Han et al, 2006). In addition, it also possessed some antiplatelet activity (Lin et al, 1996). Cyanomaclurin (4) inhibited mushroom tyrosinase activity with an IC 50 value of 68.7 mM (Zheng et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of flavonoids and prenylflavonoids have been isolated from this plant (Chung et al, 1995;Lin et al, 1995). Their biological effects have also been reported, including anti-inflammatory (Wei et al, 2005) (Zheng et al, 2008), cytotoxicity (Arung et al, 2010), antiplatelet (Lin et al, 1996), and antibacterial activities .…”
Section: Introductionmentioning
confidence: 99%